Alasan Pemerintah Arab Saudi Mendukung China dalam Kasus Diskriminasi Muslim Uighur - Putri, Yesya Ichsaniah; Ahmadi, Sidiq (POLITEA, 2021)
This journal article focuses on the issue of discrimination against Uighur Muslims in China. The purpose of this study is to describe the response of Saudi Arabia to the discrimination cases against Uighur Muslims in China. This study also tries to find out the reason behind the response and Saudi Arabia's policies on this issue. This is a qualitative research, using Rational Choice approach to analyze the attitude of Saudi Arabia’s government behind their decision, and the source of analysis come from the articles and journals. Based on the analysis, this research found that there is one strong reason why Saudi Arabia chose to remain silent about the discrimination cases of Uighur Muslims and sided with China when western countries condemned the Chinese government's actions against discrimination Uighur Muslims. Furthermore, this research is limited in scope by only discussing and focusing in economic, so this research can be refined by further research by discussing and focusing on several things that have not been explained in more detail in this study.